Gender and agriculture in the information society - Hambly Odame, Helen; Hafkin, Nancy; Wesseler, Gesa; Boto, Isolina (ISNAR and CTA, 2002)
Excitement about new information and communication technologies (ICTs) is tempered by long-standing problems of gender inequality in development processes. In most developing countries, women make up the majority of the population working in agriculture, but they are marginalized with respect to access to ICTs for economic and social empowerment. Moreover, two-thirds of the world’s 876 million illiterates are women, most of whom live in rural areas of developing countries.